Pelanggaran Hak Kekayaan Intelektual (HaKI) dalam Perspektif Hukum Islam - Mustofa, Imam (Fakultas Syariah IAIN Purwokerto, 2010)
The study of violation toward intellectual property from the Islamic law perspective is not much. Meanwhile, it really needs protection from the laws itself. This paper begins its discussion with the protection of property in Islam, the importance of fiqh for intellectual property, defining the violation law toward intellectual property and the last point is about the violation from a fiqh perspective.